Effects of activated charcoal on the root orientation of Anthurium andraeanum and Chrysanthemum morifolium cultured in vitro - Nhat Linh, Nguyen Thi; Nam, Nguyen Ba; Kim Yen, Nguyen Thi; Cuong, Le Kim; Huy, Nguyen Phuc; Nhut, Duong Tan (Academia Journal of Biology, 2012)
Activated charcoal (AC) is usually used in culture media to enhance the growth and development of in vitro plants, however, the effective ness of root orientation of AC has not yet been investigated. Therefore, the precursor of root orientation designs was carried out by dividing media into two parts, AC-free part and AC part with the optimal investigated concentrations, 2 g/l AC for Anthurium andraeanum and 3 g/l AC for Chrysanthemum morifolium and then examining effects of positions of AC part (top, center or bottom). The results showed that most of the developing roots occurred in the AC parts (over 80%). Moreover, the root orientation of A. andraeanum was more considerable than that of C. morifolium. In addition, position of AC part in the bottom was the best for the growth and development of in vitro roots and shoots of A. andraeanum and C. morifolium. Besides, plantlets were grown and developed well in vitro conditions also have good growth and development in ex vitro conditions. The results have a great signification in plant micropropagation.